Pengaruh Corporate Governance dan Intellectual Capital terhadap Nilai Perusahaan - Anthony Holly; Robert Jao; Ana Mardiana; Yulisna Bunga (Faculty of Economics and Business, Universitas Mahasaraswati Denpasar, 2024)
This research aims to examine the influence of corporate governance (board direction, managerial ownership, institutional ownership, and audit committee) and intellectual capital on company value. Company value is measured using Tobin's Q. This research uses secondary data. The sampling technique used was purposive sampling, with a sample of 43 manufacturing companies listed on the Indonesia Stock Exchange in 2020-2022. The analytical method used is multiple regression analysis. Based on regression analysis, the results of this research show that board direction has an insignificant positive effect on company value. Managerial ownership has a significant negative effect on firm value. Institutional ownership has a significant negative effect on firm value. The audit committee has an insignificant negative effect on company value and intellectual capital has an insignificant negative effect on company value.